11 books expanding Tan Lin's Seven controlled vocabularies and obituary 2004 - Lin, Tan 1957-; Snelson, Daniel (Edit Publications, 2010)
This book is an inventory, map, and documentation of the tools, software, resources, people, contributions, and publications connected with the event. All devices are also documented individually as photos, ...
Keywords: Künstlerbuch